Energy Strategy and Transition to Green Energy in Japan - Z. S. Podoba (Russian Japanology Review)
The paper presents an analysis of the current state of green energy in Japan. The study showcases that Japan’s energy strategy focuses primarily on eliminating energy deficit and, secondly, on greening the sector. After the Fukushima accident, Japan recognized renewable energy as a solution to the energy security problem and intensified government policies to stimulate investment in renewable energy. Policy incentives, primarily the introduction of feed-in tariffs, and massive investments have led to an increase in the share of renewable energy sources, especially solar PV, in the structure of electricity generation, and contributed to CO2 emissions decline after 2013, as well as the improvement in the energy efficiency of the economy. By the end of the second decade of the 21st century, Japan was among the top- five countries based on installed renewable power capacity (excluding hydropower). However, the costs of electricity have been rising and the costs associated with installing renewables in Japan are very high comparing with other countries. Meanwhile, Japan is among the top-five economies with the highest CO2 emissions, 90 percent of which are energy-related, and has been criticized by the international community for its ongoing support for fossil fuels. In 2020, Japan announced an ambitious plan to achieve carbon neutrality by 2050 by speeding up the development of key technologies such as next generation solar batteries and carbon recycling. The promotion of hydrogen society is called one of the most important steps towards a low-carbon economy in Japan. Achieving the goal will require a significant revision of the current energy plan, according to which, by 2030, more than half of the country’s energy will continue to be produced by fossil fuel plants. Japan has made some progress in its green energy policy, but whether it is sustainable remains to be seen. In addition, in light of low oil prices and the COVID-19 recession, the future of renewable energy sources remains uncertain.